You are on page 1of 10

# ECE 308 -12

## The One-Side z-Transform

Z. Aliyazicioglu
Electrical and Computer Engineering Department
Cal Poly Pomona

## The One-Side z-Transform

The one-sided z-transform of a signal x(n) is defined as

X + ( z ) = x ( n) z n
n =0

z+

x (n) X + ( z )

## The one-sided z-transform has the following characteristics:

1. It does not contain information about the signal x(n) for negative
values of time (i.e., for n<0)
2. It is unique only for causal signals, because only these signals are
zero for n<0.
3. The one-sided z-transform X+(z) of x(n) is identical to the two-sided
z-transform of the signal x(n)u(n).
4. ROC of X+(z) is always the exterior of the circle. So it is not
necessary to refer to their ROC

ECE 308-12 2

## The One-Side z-Transform

Example:
x+

x1 (n) = {1,2,5,7,0,1} X 1+ ( z ) = 1 + 2 z 1 + 5 z 2 + 7 z 3 + z 5

z+

x2 (n) = {1,2,5,7,0,1} X 2+ ( z ) = 5 + 7 z 1 + z 3

x+

## x3 (n) = {0,0,1, 2,5,7,0,1} X 3+ ( z ) = 1z 2 + 2 z 3 + 5 z 4 + 7 z 5 + z 7

x+

x+

x4 (n) = (n) X 4+ ( z ) = 1

x5 (n) = (n k ) X 5+ ( z ) = z k
+

x
1
+
n
x6 (n) = (n + k ) X ( z ) = 0 x4 ( n) = a u ( n) X 4 ( z ) = 1 az 1

x+

+
6

ECE 308-12 3

## The One-Side z-Transform

Shifting Property
Case 1:Time Delay
if

x+

x ( n) X + ( z )
k
x

x ( n k ) z k X + ( z ) + x ( n) z n
n =1

Then
,.

x+

x (n k ) z k X + ( z )

## In case x(n) is causal, then

Example:

x+

x ( n) = a n u ( n) X + ( z ) =

k >0

k >0

1
1 az 1

x1 (n) = x(n 2)

The z-transform of
+

x
1

x(n 2) = a n2u (n 2) z 2
+ x(1) z + x(2) z 2
1
1 az

2
z
=
+ x(1) z 1 + x(2)
1 az 1

ECE 308-12 4

## The One-Side z-Transform

x+

if

x ( n) X + ( z )
+

k 1
x

x ( n + k ) z k X + ( z ) x ( n) z n
n =0

Then
Example:

x+

x( n) = a n u ( n) X + ( z ) =

k >0

1
1 az 1

x1 (n) = x(n + 2)

The z-transform of

x
1

x ( n + 2) = a n + 2u ( n + 2) z 2
+ x (0) + x (1) z 1
1
1 az

2
z
=
+ x (0) z 2 + x (1) z
1 az 1
z2
=
+ z 2 + az
1 az 1

ECE 308-12 5

## The One-Side z-Transform

Final Value Theorem:
x+

if

x ( n) X + ( z )
x+

Then

n

z 1

## This is exits if the ROC of ( z 1) X + ( z ) includes the unit circle.

Example:

x (n) = u ( n)

Y ( z) = H ( z) X ( z) =

h( n) = n u ( n)

y ( n ) = h ( n) * x ( n )

1
z2
=
1
1 z 1 z
( z )( z 1)

ROC

z >

z2
z2
=
( z )( z 1) ( z )

ROC

z >

( z 1)Y ( z ) = ( z 1)

x+

n

z 1

z2
1
=
z 1

ECE 308-12 6

## The One-Side z-Transform

Solution of Difference Equation:
The one-sided z-transform is a very efficient tool for the solution of
difference equation.

y ( n) = y (n 1) + y (n 2)

Example:
,

y (1) = 0 y ( 2) = 1

## Y + ( z ) = z 1 Y + ( Z ) + y (1) z + z 2 Y + ( z ) + y (1) z + y (2) z 2

Y ( z ) = z 1Y + ( Z ) + y ( 1) + z 2Y + ( z ) + z 1 y (1) + y (2)
Y ( z )(1 z 1 z 2 ) = 1

Y ( z) =

1
1 z 1 z 2

z2
z2 z 1
ECE 308-12 7

## The One-Side z-Transform

Example:(cont)
Y ( z) =

A1 = (1 1.618 z 1 ) Y ( z )
=

1
1

1 + .618

1.618

z 1 =

1
1.618

A2

1
1
.618
+
z 1 )
(

1
1
1.618

z 1 )
(

z 1 =

1
1.618

= 0.7236

A2 = (1 + 0.618 z 1 ) Y ( z )
=

A1

## (1 1.618 z )(1 + 0.618z ) (1 1.618z ) (1 1.618z )

z 1 =

1
0.618

z 1 =

1
0.618

1
= 0.2764
1

1
1.618(
)

0.618

Finally
n
n
y ( n ) = 0.7236 (1.618 ) 0.2764 ( 0.618 ) u (n )

ECE 308-12 8

Example:

## Find the step response of the system

y ( n) = y (n 1) + x ( n) 1 < < 1
The initial condition

y ( 1) = 1

## Taking one-sided z-transform

Y + ( z ) = z 1Y + ( Z ) + y (1) + X + ( z )
Y + ( z ) = z 1Y + ( Z ) + y (1) +
Y + ( z) =

1 z 1

## The inverse transform

1
1 z 1

1
(1 z 1 )(1 z 1 )

y (n) = n+1u ( n) +
=

1 n+1
u ( n)
1

1
(1 n+2 )u (n)
1

ECE 308-12 9

## The One-Side z-Transform

Analysis of LTI Systems in the z-Domain
Response of System with Rational System Function
Let us assume that the input signal x(n) and the corresponding
system function h(n) have rational z-transform X(z) and H(z) of
the form
X ( z) =

N ( z)
D( z )

H ( z) =

and

B( z )
A( z )

## If the system initially relaxed (initial conditions for difference

equation are zero ), the z-transform of system output has
Y ( z) = H ( z) X ( z) =

B( z ) N ( z )
A( z ) D ( z )

## Partial fraction expansion of Y(z) will be in the following form if no

pole-zero cancellation
N

L
Ak
Qk
+

1
1
k =1 1 p x z
k =1 1 q x z

Y ( z) =

where
q1, q2 ,...qL

system poles,
the input signal poles,
and p qm
ECE 308-12 10 k

p1, p2 ,... pN

## The One-Side z-Transform

The inverse transform of Y(z) yields
N

k =1

k =1

y (n) = Ak ( pk ) n u (n) + Qk ( qk ) n u ( n)

## where Ak and Qk are functions of both sets of poles pk and

qk.
We can separate the y(n) into two parts
N

ynr ( n) = Ak ( pk ) n u ( n)

natural response

k =1

## Natural response is different than zero-input response. If

X(z) is zero, then Y(z) is zero
L

y fr ( n) = Qk ( qk ) n u (n)

k =1

ECE 308-12 11

## The One-Side z-Transform

Response of Pole-zero System with Nonzero Initial Condition.
The input signal x(n) is assumed to be causal. The effect of all
previous input signals to the system are reflected in the initial
conditions y(-1), y(-2), ..y(-N). We will look at the one-sided ztransform
N
k

M
Y + ( z ) = ak z k Y + ( z ) + y (n) z n + bk z k X + ( z )
k =1
k =1

k =1

X + ( z) = X ( z)

## Since x(n) is causal, we can set

M

Y ( z) =

b z
k =1
N

1 + ak z k

X ( z)

a z y ( n) z
k

k =1

k =1

Y + ( z) = H ( z) X ( z)

k =1
N

1 + ak z k
k =1

N0 ( z)
A( z )

k =1

k =1

N 0 ( z ) = ak z k y ( n ) z n
ECE 308-12 12

## The One-Side z-Transform

The output of the system can subdivide into two parts.

Yzi+ ( z ) =

N0 ( z)
A( z )

gives us y(n)

ECE 308-12 13

## The One-Side z-Transform

Example:
Determine the unit step response of the system of the
following equation.

y ( n) = 0.9 y ( n 1) 0.81 y ( n 2) + x( n)
Condition: a.
b.

y (1) = y (2) = 0
y ( 1) = y (2) = 1

Solution:
Y ( z ) = 0.9 z 1Y ( z ) + y (1) 0.81 z 2Y ( z ) + z 1 y (1) + y (2) + X ( z )
Y ( z )(1 0.9 z 1 + 0.81z 2 ) = 0.9 y (1) 0.81z 1 y (1) + 0.81 y (2) + X ( z )
Y ( z) =

1
X ( z)
(1 0.9 z + 0.81z 2 )

## The system function is

H ( z) =

1
(1 0.9 z + 0.81z 2 )
1

ECE 308-12 14

Example: (cont)

p1 = 0.9e

and

p2 = 0.9e

X ( z) =

Therefore,

1
(1 z 1 )
1

Y ( z) =

Y ( z) =

0.544e j 95.2
j

(1 0.9e z )
3

3

0.544e j 95.2
j

(1 0.9e z )
3

1.099
(1 z 1 )

3

ECE 308-12 15

Example(cont)

## Y ( z )(1 0.9 z 1 + 0.81z 2 ) = 0.9 0.81z 1 + 0.81 + X ( z )

Y ( z) =

1
0.81 0.81z 1
X ( z)
(1 0.9 z 1 + 0.81z 2 )
(1 0.9 z 1 + 0.81z 2 )

Yzi ( z ) =
Yzi ( z ) =

0.81 0.81z 1
N0 ( z )
=
A( z ) (1 0.9 z 1 + 0.81z 2 )
0.4956e j 84.8
j

1 0.9e 3 z

0.4956e j 84.8
j

1 0.9e 3 z 1

3

## The total response

Y ( z ) = Yzs ( z ) + Yzi ( z )

3

ECE 308-12 16

## The One-Side z-Transform

The response of a system to a given input can be separated
into two components
N

## ynr (n) = Ak ( pk ) n u (n)

Natural response

k =1

where pk i = 1,2,..., k , are the poles of the system and Ak are scale factor.
If pk < 1 for all k, ynr (n) goes zero for n approaches infinity. In this
case, natural response of the system accept as transient response.
The forced response:

y fr ( n) = Qk ( qk ) n u (n)
k =1

where qk,i = 1,2,..., k are the poles in the forcing function and are Qk
scale factor.
ECE 308-12 17

## The One-Side z-Transform

If qk < 1 for all k, y fr (n) goes zero for n approaches infinity
If the causal input signal is sinusoidal, then the forced signal
will be sinusoidal for all n 0 . In the case, the forced response
Example:

## Find the transient and steady-state response of

y (n) = 0.5 y (n 1) + x(n)

x(n) = 10cos(

n
4

)u (n)

## The system is initially relaxed.

Solution:

Y ( z ) = 0.5 z 1Y ( z ) + X ( z )
H ( z) =

1
Y ( z)
=
X ( z ) 1 0.5 z 1

The poles at

z = 0.5

ECE 308-12 18

## The One-Side z-Transform

Example: (cont)
The z-transform of input signal
1 z 1 cos

X ( z ) = 10

1 2 z 1 cos

1 1
z )
2
=
1 2 z 1 + z 2
10(1

+ z 2
4
1 1
z )
10(1
2
X ( z) =
j / 4 1
(1 e z )(1 e j / 4 z 1 )

1 1
z )
2
Y ( z) = H ( z) X ( z) =
j / 4 1
1
(1 0.5 z )(1 e z )(1 e j / 4 z 1 )
10(1

Y ( z) =

A3
A1
A2
+
+
(1 0.5 z 1 ) (1 e j / 4 z 1 ) (1 e j / 4 z 1 )

1 1
z )
2
A1 =
1
(1 2 z + z 2 )
10(1

1
2)
2
=
= 1.907
z 1 = 2
(1 22 + 22 )
10(1

ECE 308-12 19

## The One-Side z-Transform

Example (cont)
1 1
z )
2
A2 =
1
(1 0.5 z )(1 e j / 4 z 1 )
10(1

1 1
z )
2
A3 =
1
(1 0.5 z )(1 e j / 4 z 1 )

z 1 =e j / 4

= 6.78e j 28.7

10(1

z 1 = e j / 4

= 6.78e j 28.7

Y ( z) =

1.907
6.78e j 28.7
6.78e j 28.7
+
+
(1 0.5 z 1 ) (1 e j / 4 z 1 ) (1 e j / 4 z 1 )

## The natural or transient response is

ynr (n) = 1.907(0.5) n u (n)

D

4

ECE 308-12 20

10